Languages and Communities in the Late-Roman and Post-Imperial Western Provinces (Oxford University Press, 2024)
Languages are central to the creation and expression of identities and cultures, as well as to life itself, yet the linguistic variegation of the later-Roman and post-imperial period in the Roman West is remarkably understudied. A deeper understanding of this important issue is crucial to any reconstruction of the broader story of linguistic continuity and change in Europe and the Mediterranean, as well as to the history of the communities who wrote, read, and spoke Latin and other languages. In spite of intensive study of culture and ethnic identity in late antiquity, language has often been neglected, a neglect encouraged by the disciplinary boundaries between linguists and historians, Romanists, and medievalists. There is no single volume that sets out the main developments, key features, and debates of the later-Roman and post-imperial linguistic environment. The linguistic landscapes of the late-Roman and post-imperial West are difficult to uncover and describe, while attempts to speak across disciplinary divides are challenging. The contributors have tackled this subject by offering detailed coverage of the Iberian Peninsula, North Africa, Gaul, the Germanies, Britain, and Ireland. This volume, the third in the LatinNow series, helps readers to understand better the embeddedness, or not, of Latin, at different social levels and across provinces, to consider (socio)linguistic variegation, bilingualism and multilingualism, and attitudes towards languages, and to confront the complex role of language in the communities, identities, and cultures of the later and post-imperial Roman West.